Removal of Arsenic(V) from aqueous solution by quaternized rice husk - Lee, C. K.; Low, K. S.; Liew, S. C.; Choo, C. S. (Taylor and Francis Group, 1999)
The potential of using quaternized rice husk (QRH) as a sorbent for the removal of As(V) from aqueous solution was investigated. Both batch and column studies were carried out. Results of batch studies indicate that sorption was pH and temperature dependent. Equilibrium was attained within 20 minutes and sorption appeared to be essentially an ion exchange process. Experimental data could be fitted into the Langmuir isotherm with a maximum sorption capacity of 18.98 mg g−1 at pH 7.5 and 28±2°C. Anions such as SO42− and CrO42− interfere with the uptake of As(V) by QRH. In the column studies, results show that breakthrough depends on bed depth but not on flow rate as sorption was very rapid. In addition, service time at 50% breakthrough was inversely proportional to influent concentration and had a linear relationship with bed-depth.